Analysis of Institutional solid waste management in Gweru Zimbabwe - Jerie, Steven (Organisation for Social Science Research in Eastern and Southern Africa, 2016)
Of all environmental problems that have come into focus in Gweru, institutional solid waste management has been the slowest to develop either direction or regulatory mechanisms. This study examines the characteristics of waste generated, and the effectiveness of the waste management system in the institutions. Measurements were used to determine the quantities of waste generated, and interviews and questionnaires were employed to assess the soundness of the system. The general picture is that significant quantities of waste are generated in the institutional sector, but there are no sound practices for managing the waste. This paper attempts to provide a framework for policy and planning strategies relating to solid waste management in public and private institutions in Gweru. Presently, institutional solid waste management is an area in which our ignorance still exceeds our knowledge.